2020
DOI: 10.3390/ijerph17176418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Suicide Prevention Program for the Energy Sector

Abstract: There is evidence indicating that traditionally male-dominated occupations are associated with greater risk of suicide. In Australia, MATES in Construction was developed as an occupational health initiative to prevent suicides in the industry. The program has recently been applied to the energy industry; however, little is known regarding exposure to suicide and suicide prevention interventions in this sector. The study aimed to examine the effectiveness of MATES in Energy general awareness training (GAT), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…In this study, participant statements echo Ross et al’s (2020) findings, who reported that 65% of the participants in their study knew someone who had attempted to end their life. Furthermore, 69% of the participants had known someone who had actually died by suicide and 2% of respondents had experienced recent thoughts of suicide.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…In this study, participant statements echo Ross et al’s (2020) findings, who reported that 65% of the participants in their study knew someone who had attempted to end their life. Furthermore, 69% of the participants had known someone who had actually died by suicide and 2% of respondents had experienced recent thoughts of suicide.…”
Section: Resultssupporting
confidence: 70%
“…Furthermore, 69% of the participants had known someone who had actually died by suicide and 2% of respondents had experienced recent thoughts of suicide. Examining the GAT (General Awareness Training) component of MATES in Energy, Ross et al (2020) found a significant increase in suicide awareness and literacy, knowledge, and improvements in attitudes to help-seeking and help-giving. Participant #12, who worked for a large oil and gas company, stated that there was an online learning module related to mental health that the company had provided access to.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MATES in Construction program was established by and for the Australian construction industry in 2007. It has also been adapted for the mining and energy sectors, and research evaluations in each sector have demonstrated the program's positive impact on participants' suicide prevention literacy, and willingness to seek and offer help [15][16][17][18]. However, the evidence to date has been limited to uncontrolled observational studies, with no experimental or randomised trial studies to date.…”
Section: Introductionmentioning
confidence: 99%